2021
DOI: 10.3390/cancers13040921
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related Carcinogenesis: Lessons from Animal Models to Clinical Aspects

Abstract: Inflammation-related carcinogenesis has long been known as one of the carcinogenesis patterns in humans. Common carcinogenic factors are inflammation caused by infection with pathogens or the uptake of foreign substances from the environment into the body. Inflammation-related carcinogenesis as a cause for cancer-related death worldwide accounts for approximately 20%, and the incidence varies widely by continent, country, and even region of the country and can be affected by economic status or development. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 167 publications
0
15
0
Order By: Relevance
“…Tumor-related inflammation has been widely studied and listed as a major phenotype of malignant tumors ( 20 ). Meanwhile, inflammatory and immune cells are important parts of the tumor microenvironment and indispensable factors in promoting tumor proliferation, tumor progression, survival and migration ( 21 ). Bladder cancer is an inflammation- and immune-related malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-related inflammation has been widely studied and listed as a major phenotype of malignant tumors ( 20 ). Meanwhile, inflammatory and immune cells are important parts of the tumor microenvironment and indispensable factors in promoting tumor proliferation, tumor progression, survival and migration ( 21 ). Bladder cancer is an inflammation- and immune-related malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Initiators of Precancerous Lesions and GC 6.1. Cytokine Genes Influence Individual Response to Carcinogenic Exposures Chronic inflammation can occur in genetically susceptible hosts with defective mucosal host defense systems or dysregulated immune responses, leading to excessively aggressive responses to ubiquitous antigens, which is the root cause of inflammationrelated carcinogenesis [20,23,105]. Inflammation-related genetic polymorphisms act as initiators of H. pylori-induced chronic atrophic gastritis, and together with other factors they become the precursor of precancerous lesions and carcinoma [106,107].…”
Section: Inflammation-related Genetic Polymorphisms Together With Other Factors Asmentioning
confidence: 99%
“…True incidence of STS in dogs is unknown but it has been previously suggested that these tumours account for 9%–15% of all cutaneous and subcutaneous canine tumours 1 . The underlying causes for sarcomas are varied and multifactorial 2–28 . In dogs, STS have been associated with radiation, trauma, chronic inflammation and parasitic infection 2–6 .…”
Section: Introductionmentioning
confidence: 99%
“…and childhood cancer. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In human medicine, approximately 25% of malignancies have been associated with chronic inflammation. 17 Traumatic injury has also been suggested to predispose people to STS development.…”
mentioning
confidence: 99%
See 1 more Smart Citation